The Effectiveness of Rational Emotive Behavior Therapy Group Counseling Self Management Techniques and Cognitive Restructuring Techniques to Reduce Student Academic Procrastination - Yusran, Iki; Purwanto, Edy; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2023)
Procrastination as an act of delaying assignments or work by doing things that are not related to assignments has the potential to become an obstacle to academic achievement. The purpose of this study was to test the effectiveness of self-management and cognitive restructuring of rational emotive behavior therapy counseling groups to reduce students' academic procrastination. By doing a pretest-posttest comparison it was applied to 12 students at SMP Negeri 3 Wangi-Wangi Selatan. The instrument used is the academic procrastination scale based on the indicators put forward. The data analysis technique used was the Mann-Whitney T-test paired sample. The results of this study indicate that the rational emotive behavior therapy group counseling approach, self-management techniques and cognitive restructuring techniques are effective in reducing students' academic procrastination. The findings of this study prove that group counseling, rational emotive behavior therapy approaches, self-management techniques and cognitive restructuring techniques are effective in reducing academic procrastination. Based on the findings of this study, a rational emotive behavior therapy group counseling intervention is recommended for counselors to reduce student academic procrastination.